Formulation and Evaluation of Herbal Lozenges of Vasaka Leaf for the Treatment of Sore Throat - , Saurabh Kumar; , Himanshi Rathaur; , Sayantan Mukhopdhyay (Archives of Current Research International, 2025)
The present study focuses on the development and evaluation of herbal lozenges formulated using the leaf extract of Justicia adhatoda (Vasaka), a medicinal plant known for its expectorant, sore throat, anti-inflammatory, and antimicrobial properties. Vasaka leaves are excellent for relieving the symptoms of a sore throat because they are high in vasacin and vasinone. Vasaka leaves were collected from the Garhwal region of Uttarakhand, Dehradun, Herbal garden of Shivalik College and extracted using the soxhlet method. Lozenges were prepared via the molding technique incorporating various excipients, including gelatin, dextrose, sorbitol, and honey, across four formulations (F1–F4). The prepared lozenges were evaluated for organoleptic properties, thickness, hardness, and disintegration time. Among all formulations, F3 demonstrated the most desirable attributes, including optimal hardness and the fastest disintegration time (16 minutes), making it the most effective for potential therapeutic use. This study supports the incorporation of traditional herbal extracts into modern dosage forms to create effective, patient-friendly alternatives for managing sore throat symptoms.